2017
DOI: 10.1108/jcm-02-2014-0869
|View full text |Cite
|
Sign up to set email alerts
|

Culture as a moderator of cognitive age and travel motivation/perceived risk relations among seniors

Abstract: Purpose This study contributes to greater understanding of the senior market and the cultural differences regarding aging in Western and Asian cultures. The review of the literature highlights the cultural differences toward the concept of aging in Asian and Western countries and describes a useful age concept for investigating senior consumers, namely, that of subjective age. The purpose of this study is to investigate the influence of subjective age dimensions on seniors’ behavior and to assess the role of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…Risks such as insecurity reduce their intention to shop online (Matic and Vojvodic, 2014). This condition is very different from the empirical results that, subjective perception of age has a positive influence on the formation of risk perception (Le Serre et al, 2017). As people get older or get older, people will consider the risks more.…”
Section: Research Gapcontrasting
confidence: 68%
“…Risks such as insecurity reduce their intention to shop online (Matic and Vojvodic, 2014). This condition is very different from the empirical results that, subjective perception of age has a positive influence on the formation of risk perception (Le Serre et al, 2017). As people get older or get older, people will consider the risks more.…”
Section: Research Gapcontrasting
confidence: 68%
“…Teller et al (2013) analyzed elderly consumers' grocery store patronage and showed that product range, maneuverability and atmosphere within the store are considered critical factors for individuals with a high cognitive age. Le Serre et al (2017) found that subjective agei.e. a concept similar to cognitive age, defined as individual's self-evaluation as belonging to a "young," "middle-aged" or "old" age group (Moschis, 2012) was related to perceived risk in the context of travel-related behavior.…”
Section: Effects Of Cognitive Age On Older Consumers' Sensation and Behaviormentioning
confidence: 99%
“…Following the comprehensive study of Nielsen (2014), the senior tourist market has encouraged researchers to investigate in this field and examine various topics, especially in relation to constraints (Huber, Milne, & Hyde, 2018); accommodation (Anuar, Musa, Khalid, & Anderson, 2017;Losada et al, 2017); length of stay and frequency of travel (Alén, Nicolau, Losada, & Domínguez, 2014;Losada, Alén, Domínguez, & Nicolau, 2016);motivation and spirituality (Alén, Losada, & de Carlos, 2015;Moal-Ulvoas, 2017;Moal-Ulvoas, 2016;Patuelli, & Nijkamp, 2016); and cognitive age (Le Serre et al, 2017).…”
Section: Background To Senior Tourismmentioning
confidence: 99%
“…Cognitive age, such as cognitive structure, stems from the field of cognitive psychology and is often used in senior consumer behavior research. The cognitive age is connected to self-perception of the individual and determines what age the person feels regardless of his/her calendar age (Le Serre et al, 2017). Barak (1987) (Sudbury & Simcock, 2009) and the motivations of tourists (González et al, 2009) have been investigated before.…”
Section: Background To Senior Tourismmentioning
confidence: 99%
See 1 more Smart Citation